Adaptation of the methodological instrument of the representation of the content (CORE) to the theoretical framework of TPCK - Boris Fernando Candela (Universidad Distrital Francisco José de Caldas, 2017)
Since the middle of the eighties the community in science education has been interested in teachers to identify and develop the Content Pedagogical Knowledge (PCK). To this end, it has designed educational programs from a "reflective orientation" perspective structured from a set of training activities whose tasks are focused on the practice of designing specific content learning environments, where the methodological instrument of the Representation of Content (CoRe) has played a critical role. The logical structure of it provides the possibility for teachers to become aware of the theoretical and methodological elements that underpin the PCK. On the other hand, with the emergence of digital technologies as an instrument for representing content and effective management of the classroom, the need to transform the construct of the Content Pedagogical Knowledge (PCK) to the Technological and Pedagogical Knowledge of the content is generated (TPCK). In this sense, it is pertinent to adapt the epistemological structure of the CoRe to the theoretical framework of the emerging construct of the TPCK, in order that this instrument continue to be used as a key heuristic in education programs where the practice of designing environments Learning is important for the professional development of teachers. Of course, the adaptation of the CoRe to the perspective of the TPCK is accompanied by a conceptualization of each of the twelve items that configure it, in order to illustrate the teachers during their development.